Cura espiritual: uma análise da experiência dos frequentadores não espíritas na Instituição Espírita de Caridade Nosso Lar, em Montes Claros, norte de Minas Gerais - Gomes, Cristiane Martins (2014)
This present work is an analysis of the experience of non-spiritists goers who seek spiritual healing as a way to solve their problems, physical, psychological and spiritual. The survey was conducted in the Instituição Espírita de Caridade Nosso Lar, in the city of Montes Claros, in the north of the state of Minas Gerais. It was sought to explore in this research the impact of the spiritual healing seen by people who do not declare themselves spiritists, but enjoyed the spiritual healing as a solution to solve their problems. It was not intended with the research to put evidence on Spiritism, but to demonstrate who are the people who make use of spiritists treatments, whether or not belonging to any religious creed. What mattered was to understand the vision of those people who seek spiritual healing being not spiritists. Based on the proposed objectives and hypotheses, three main issues were analyzed: the reason that led non-spiritists to the Instituição Espírita de Caridade Nosso Lar; the changes perceived by them in their faith; and the necessity to know if the spiritual healing really brought some benefit to people seeking this alternative means and if the treatment they received caused in them religious or spirituals changes. To achieve that the researcher drew on a specially developed questionnaire for this investigation, applied to about 40 non-spiritists who attended at the spiritist center under study during the years 2013 and 2014. It was also done a critical reading of data arising from the survey of responses to the questionnaire